2020
DOI: 10.1021/acs.bioconjchem.0c00482
|View full text |Cite
|
Sign up to set email alerts
|

Modular Conjugation of a Potent Anti-HER2 Immunotoxin Using Coassociating Peptides

Abstract: Immunotoxins are emerging candidates for cancer therapeutics. These biomolecules consist of a cell targeting protein combined to a polypeptide toxin.Associations of both entities can be achieved either chemically by covalent bonds or genetically creating fusion proteins. However, chemical agents can affect activity and/or stability of the conjugate proteins and additional purification steps are often required to isolate the final conjugate from unwanted by-products. As for fusion proteins, they often suffer fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Because V H Hs display unique properties, such as high solubility and a reversible unfolding reaction under stringent conditions (Muyldermans, 2013), E3 small peptide is of particular interest for dimerization of V H Hs. Indeed, we have previously reported that E3 peptide is robust at low pH, form in complex media and resists thermal denaturation above 90°C (Stoessel et al, 2020;Vigneron et al, 2019), making it a powerful tool for bivalent V H Hs engineering.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because V H Hs display unique properties, such as high solubility and a reversible unfolding reaction under stringent conditions (Muyldermans, 2013), E3 small peptide is of particular interest for dimerization of V H Hs. Indeed, we have previously reported that E3 peptide is robust at low pH, form in complex media and resists thermal denaturation above 90°C (Stoessel et al, 2020;Vigneron et al, 2019), making it a powerful tool for bivalent V H Hs engineering.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently taken advantage of a modified tetramerization domain of p53 to construct bifunctional and bispecific heterotetramer biomolecules (Stoessel et al, 2020;Vigneron et al, 2019). This tetramerization domain (p53tet) is a small peptide of 31-aminoacids, which can be fused to various moieties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 These E-and K-enriched sequences, named E3 and K3 respectively, were recently demonstrated to conveniently favour the selective non-covalent union of 2 distinctly tagged functional proteins into highly stable heterotetramers even in complex biological fluids crowded with all sorts of proteins and diverse compounds. 18,33 First, the Nb was genetically engineered at its C-terminal end with the aspartate-enriched variant of the p53 heterotetramer domain (E3) along with a polyhistidine sequence (Figure 2). 18 The recombinant Nb-E3 fusion protein was then produced in E. coli and purified by immobilized metal affinity chromatography followed by size exclusion chromatography (SEC) with high yield and purity (Figure 2B).…”
Section: Synthesis Of Gfp Nanobody-aunp Conjugatementioning
confidence: 99%
“…30 To design Nb-AuNP conjugates with usefulness for gold immunolabelling application of cellular specimen, we explored methods for strongly linking thionitrobenzoates-coated AuNPs (AuG) 31,32 to bioengineered GFP binding Nbs. 8,20 We discovered that the non-covalent conjugation approach based on the complementary associating dimers originating from a p53 heterotetramer variant, 17,18,33 led to Nb:AuNP assemblies with excellent immunogold labelling abilities (Figure 1).…”
Section: Introductionmentioning
confidence: 99%